2011
DOI: 10.1039/c1an00013f
|View full text |Cite
|
Sign up to set email alerts
|

Determination of melamine in milk powder based on the fluorescence enhancement of Au nanoparticles

Abstract: We have developed a new analytical method to detect melamine (MA) in milk powder based on the fluorescence enhancement of Au nanoparticles (AuNPs). AuNPs with the average diameter of ∼16 nm can emit stable fluorescence at 370 nm when the excitation wavelength was selected at 252 nm. The AuNPs could assemble with melamine to form larger aggregates (AuNPs-MA) through electrostatic interaction and coordinating interaction in acidic conditions, which led to the significant enhancement of the fluorescence intensity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 32 publications
0
31
0
Order By: Relevance
“…Some new methods based on luminescence phenomena were proposed recently for the determination of melamine: complexation with a fluorescent sensor (cucurbit-7-uryl, for example) (Zhou, Yang, Liu, Wang, & Liu, 2010), electroluminescence enhancement of Ru(bpy) 3 2þ (Guo, Gai, et al, 2011), resonance energy transfer and fluorescence enhancement by gold nanoparticles (Guo, Zhong, et al, 2011;Xiang, Zeng, Zhai, Li, & He, 2011) and the use of the Mannich reaction (Rima, Assaker, Omar, & Karim, 2013). However, none of these studies employed measurements of the natural fluorescence of melamine, as recently shown and applied for its determination in kitchen plastic ware (Finete, Gouvêa, Marques, & Pereira Netto, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Some new methods based on luminescence phenomena were proposed recently for the determination of melamine: complexation with a fluorescent sensor (cucurbit-7-uryl, for example) (Zhou, Yang, Liu, Wang, & Liu, 2010), electroluminescence enhancement of Ru(bpy) 3 2þ (Guo, Gai, et al, 2011), resonance energy transfer and fluorescence enhancement by gold nanoparticles (Guo, Zhong, et al, 2011;Xiang, Zeng, Zhai, Li, & He, 2011) and the use of the Mannich reaction (Rima, Assaker, Omar, & Karim, 2013). However, none of these studies employed measurements of the natural fluorescence of melamine, as recently shown and applied for its determination in kitchen plastic ware (Finete, Gouvêa, Marques, & Pereira Netto, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…One possible explanation is that the biological buffers temporally cross-linked the integrated nanoparticles together ( Figure S5b), which limited their mobility, thus decreasing the collision probability between the nanoparticles. As a result, the external energy transfer rate and quantum yield could be increased, as suggested in ref 39. Similarly, the temporal nanoparticle cross-linking could increase the local protein concentration; it was observed that protein adsorption led to an increase in the fluorescent intensity of Au nanoclusters.…”
Section: ■ Results and Discussionmentioning
confidence: 88%
“…It has widely used in plastics, coatings, dishware, adhesives and flame retardant materials (Andersen et al, 2008;Kim et al, 2008). Previously Kjeldahl method was used for determination of melamine in food and food products (Xiang, Zeng, Zhai, Li, & He, 2011). Therefore, melamine can be added to adulterate protein-rich diets by unethical manufacturers.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the illegal addition of melamine into milk products and infant milk are occurred. Up to now, several analytical techniques are available, such as spectrophotometry (Liu et al, 2011), colorimetric method (Wu et al, 2011), fluorescence (Xiang et al, 2011), chemiluminescence analysis (Zeng, Yang, Wang, Li, & Qu, 2011), gas chromatography (GC) (Yokley, Mayer, Rezaaiyan, Manuli, & Cheung, 2000), high performance liquid chromatography (HPLC) (Ehling, Tefera, & Ho, 2007), high performance liquid chromatography/mass spectrum (HPLC/MS) (Kim et al, 2008), sweeping micellar electrokinetic chromatography (SMEC) (Wu et al, 2011), surface enhanced raman spectroscopy (Lin et al, 2008) and capillary zone electrophoresis/mass spectrum (CE/MS) (Cook, Klampfl, & Buchberger, 2005). However, these conventional spectrophotometry and colorimetric methods are easily interfered by other related substances.…”
Section: Introductionmentioning
confidence: 99%